Nimbolide-induced oxidative stress abrogates STAT3 signaling cascade and inhibits tumor growth in transgenic adenocarcinoma of mouse prostate model - Zhang, J.; Ahn, K.; Kim, C.; Shanmugam, M.; Siveen, K.; Arfuso, Frank; Samym, R.; Deivasigamani, A.; Lim, L.; Wang, L.; Goh, B.; Kumar, Alan Prem; et al. (2016)
AIMS: Prostate cancer (PCa) is one of the most commonly diagnosed cancers worldwide. Currently available therapies for metastatic PCa are only marginally effective; hence novel treatment modalities are urgently required. Considerable evidence(s) suggest that deregulated activation of oncogenic transcription factor, signal transducer and activator of transcription 3 (STAT3) plays a pivotal role in the development and progression of PCa. Thus agents that can abrogate STAT3 activation could form the basis of novel therapy for PCa patients. In the present study, we analyzed whether the potential anticancer effects of nimbolide (NL), a limonoid triterpene derived from Azadirachtaindica, against PCa cell lines and transgenic adenocarcinoma of mouse prostate (TRAMP) model are mediated through the negative regulation of STAT3 pathway. RESULTS: Data from the in vitro studies indicated that NL could significantly inhibit cell viability, induce apoptosis and suppress cellular invasion and migration. Interestingly, NL also abrogated STAT3 activation, and this effect was found to be mediated via an increased production of reactive oxygen species (ROS) due to GSH/GSSG imbalance. Oral administration of NL significantly suppressed the tumor growth and metastasis in TRAMP mouse model without exhibiting any significant adverse effects. INNOVATION: The present study demonstrates the critical role of GSH/GSSG imbalance-mediated ROS production contributing to the STAT3 inhibitory and tumor suppressive effect of NL in PCa. CONCLUSION: Overall our findings indicate that NL exhibits significant anticancer effects in PCa that may be primarily mediated through the ROS-regulated inhibition of STAT3 signaling cascade.